Reshaping global value chains in light of COVID-19 implications for trade and poverty reduction in developing countries - Brenton, Paul 1961-; Ferrantino, Michael Joseph; Maliszewska, Maryla 1973- (World Bank Group, 2022)
Global value chains (GVCs) have driven dramatic expansions in trade, productivity, and economic growth in developing countries over the past three decades. Reshaping Global Value Chains in Light of COVID-19: Implications for Trade and Poverty Reduction in Developing Countries examines the economic impact of the COVID-19 (coronavirus) pandemic on GVCs and explores whether they can continue to be a driver of trade and development. The book undertakes the following: -- Assesses what the impact of previous crises, such as the global financial crisis of 2008-09, can say about of the resilience of GVC firms to shocks -- Examines what high-frequency data on trade flows can show about the impact of COVID-19 during the sharp global recession of 2020 -- Uses discussions with GVC firms to gain a deeper understanding of the impacts of-and their responses to-the COVID-19 shock -- Explores simulations from a global economic model to assess the potential longer-term impacts of COVID-19 on low- and middle-income countries and key factors shaping the global economy, including the evolving role of China, the rise of trade restrictions, and policy responses to global warming -- Asks what steps countries and international institutions can take to enhance the resilience of GVCs in low-income countries to future shocks. The analysis shows that well-operating GVCs are a source of resilience more than a source of vulnerability. Moreover, steps to maintain and enhance trade contribute to managing a crisis and recovery, while measures to reshore production make all countries worse off. This economic crisis offers countries an opportunity to reshape the global economy into a greener, more resilient, and inclusive system that is better equipped for a changing world. Trade is a powerful tool for achieving this aim
Keywords: Coronavirus; COVID-19; Global Value Chain; Labor Market; Pandemic Impact